Physicochemical Properties Of Pre-Treated Cuttlebone Powder And Its Potential As An Alternative Calcium Source - Yang, Wen Huey
This study was aimed to investigate the potential use of pre-treated cuttlebone powder (CBP) as an alternative calcium source by evaluating the physicochemical properties of CBP pre-treated with distilled water (CBP1), 1% acetic acid (CBP2) and 2% sodium hydroxide (NaOH) solutions (CBP3). Pre-treatments were used to extract ash and degrade the organic matters such as proteins and fats. The chemical properties including proximate composition, mineral contents and bioactive compounds as well as physical properties, including colour, bulk density, flowability, water and oil holding capacities and water solubility, of the samples were then determined. Proximate analysis revealed ash as the major component of all samples. Qualitative analysis of bioactive compounds was conducted on polysaccharides extracted from cuttlebone, and the presence of phenols, flavonoids, alkaloids and glycosides were detected. Tannins appeared to be absent in cuttlebones. Mineral analysis indicated that pre-treated CBP was rich in calcium, which means the material may be considered as a potential calcium source for food products or calcium supplements. The mineral contents of all samples increased in the order of iron < potassium < magnesium < sodium < calcium. No significant difference (p>0.05) in the whiteness and redness of all samples was observed, but the yellowness of CBP1 was significantly greater than those of CBP2 and CBP3. The bulk density of CBP2 was significantly lower (p<0.05) than those of CBP1 and CBP3, and the water holding capacity (WHC) of CBP1 was significantly higher (p<0.05) than those of CBP2 and CBP3. No significant differences (p>0.05) in oil holding capacity (OHC) and water solubility were observed amongst the samples. The high bulk density, water and oil holding capacities of pre-treated CBP demonstrated its potential use as a functional food ingredient.